KEMAMPUAN PRAGMATIK MAHASISWA TINGKAT II JURUSAN BAHASA PRANCIS, FBS-UNJ - Asti Purbarini; Amalia Saleh; Ratna Ratna (BAHAS, 2009)
The objective of this study is to find out the information about pragmatics competence of second year student in the French Department, State University of Jakarta (UNJ) Jakarta. The writers believed that it is important to conduct this study, because pragmatics competence actually is not taught explicitly in the French Department. Meanwhile, pragmatics competence plays an important role both in oral and written communication. It is hope that this study can give the contribution to the French Department especially to French curriculum department. This study was conducted on July in 2007 in the French Department, UNJ Jakarta. It was conducted through descriptive analytical interpretative by analysing the result of students’ pragmatics competence test. The population of this study is 35 French students of UNJ Jakarta who have completely taken all language skills subject. The instrument of this study is the test of pragmatics competence, which consists of 40 questions in form of multiple choices. The process of pragmatics test designing was based on the themes that have been learnt during learning process. In the French Department, pragmatics is not taught explicitly but it is integrated in the language skills subject such as writing, reading, speaking and listening. The data showed that there are 10 questions which cannot be answered correctly by the students. It is because the number of errors done by the students ranges from 18 to 30. In contrast, there are 20 questions which can be answered correctly by the students. It is because the number of errors done by the students ranges from 1 to 8. The result of this study showed that the students already have a good understanding of pragmatics which is practically integrated in the language skills subject. In addition, student’s pragmatics competence relates thoroughly to his/her creativity. To summarize, if the student is creative, he/she will then be able to use the language relevant to the context occurred, or in other words, he/she understands well the pragmatics. It is therefore important for the teachers to develop students’ pragmatics competence by exposing them to practicing the language in various setting. Kata Kunci : kemampuan, prakmatik mahasiswa